2023
DOI: 10.1002/nafm.10865
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Comparison of Age Estimates for Smallmouth Buffalo in Oklahoma Based on Otoliths, Pectoral Fin Rays, and Opercula

Abstract: With an increased interest in nongame fishes such as buffalofishes (Catostomidae, Ictiobus), there is a need for better foundational data on their life history. Bigmouth Buffalo I. cyprinellus, for example, have been found to live for more than a century. Age estimates for other sucker species have similarly suggested long life spans, but validation studies as reference points are often lacking. We conducted a 3-year study on Smallmouth Buffalo I. bubalus in Oklahoma to validate annual increments on three hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Fishes provide an excellent opportunity to understand age demographics of wild populations because most species can be aged directly via the thin-sectioned otolith 47 , 56 . Indeed, this technique also allows for age validation of long-lived species 47 , which has been rigorously demonstrated for buffalofishes 16 , 19 , 33 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fishes provide an excellent opportunity to understand age demographics of wild populations because most species can be aged directly via the thin-sectioned otolith 47 , 56 . Indeed, this technique also allows for age validation of long-lived species 47 , which has been rigorously demonstrated for buffalofishes 16 , 19 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about Arizona buffalofishes since the 1970s. New sport fisheries have emerged including catch-and-kill bowfishing, which has raised substantial conservation concern nationwide 16 21 , 31 33 , but conservation angling of buffalofishes (this study) has not previously been reported. Such activities, in practice, imply new game fish status to these species because they are recreationally pursued.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations